Անձի հոգեբանական պաշտպանական մեխանիզմների և անձնային կառույցների փոխպայմանավորվածությունը դեռահասության տարիքում - Ժամկոցյան, Ռուզաննա (Զանգակ հրատ.)
The implementation of psychological defense mechanisms depends on the level of development of individual personality. An important factor in the formation and development of mature defense mechanisms in adolescence is the development of adolescent intelligence and will. Использование психологических защитных механизмов обусловлено уровнем развития личностных структур человека. В подростковом возрасте важным фактором формирования и развития защитных механизмов является развитие интеллекта и воли.
Keywords: Հոգեբանություն